Legal Protection for Consumers in Online Buying and Selling Transactions According to Positive Law in Indonesia - Yulinda, Kiki; Tiara, Dora; Mene, Meydianto (LPPM Universitas Ekasakti, 2024)
Law Number 8 of 1999 addressing Consumer Protection is specifically delineated through Government Regulation (PP) Number 71 of 2019, which pertains to the Implementation of Electronic Systems and Transactions. Conventional business transaction modalities are categorized as electronic transactions, which are defined as legal actions executed via computers, computer networks, and/or alternative electronic media. The transactional framework facilitated by internet technology renders numerous advantages, both for vendors and consumers, as this system possesses inherent benefits that provide enhanced convenience, rapidity, and efficiency. Consequently, it is not unexpected that the current proliferation of internet utilization grounded in electronic commerce (commonly denoted as e-commerce) is experiencing swift growth, notably within the Indonesian context. This advancement simplifies the process for individuals and enterprises to engage in a diverse array of business transactions, particularly in the realm of trade.